UJI BEBAN KERJA ALAT PENGGILING TULANG SAPI (Test of the effect of Workload Dry Cow Bone Miller) - Safriyanto Safriyanto; Saipul Bahri Daulay; Nazif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT The existance of livestock waste increase in accordance with the consumption of livestock meat livestock waste itself can be faeces, bone, blood, and hair. The handling of this wastes must be done correctly so that they doesn’t contaminate the environment. One of the product that can be produced from the processing of livestock waste is bone powder which can be used as the mixture of animal feed because it’s rich in calcium and phosphorus. The aim of this research was to test of the effect of workload Dry Cow Bone Miller, with the parameters of effective capacity, yield and power, then analyze the economic value of dry cow bone miller.This research was conducted in August until October 2016 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, by literature study, testing of equipment and parameters observation. Parameters measured were effective capacity, yield and power. The results showed that the workload was significantly affected the effective capacity, yield and power. Key words: Dry Cow Bone Miller, Bone Waste ABSTRAK Keberadaan limbah hewan ternak meningkat seiring dengan tingginya konsumsi daging hewan ternak. Limbah ternak sendiri dapat berupa kotoran, tulang, darah, dan bulu. Penanganan limbah ini harus dilakukan dengan tepat agar tidak mencemari lingkungan. Salah satu produk yang dapat dihasilkan dari pengolahan limbah ternak adalah tepung tulang yang dapat dimanfaatkan sebagai campuran pakan ternak karena kaya akan kalsium dan fosfor. Penelitian ini bertujuan untuk menguji beban kerja alat penggiling tulang sapi dengan parameter kapasitas efektif, rendemen, dan daya, kemudian menganalisis nilai ekonomis alat penggiling tulang sapi.Penelitian ini dilakukan pada bulan Agustus hingga Oktober 2016 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara, Medan, dengan cara studi literatur, pengujian alat dan pengamatan parameter. Parameter yang diamati adalah kapasitas efektif alat,  rendemen, dan daya. Hasil penelitian menunjukkan bahwa beban kerja berpengaruh nyata terhadap kapasitas efektif alat, rendemen dan daya.   Kata kunci: Alat Penggiling Tulang Sapi Kering, Limbah Tulang